Assessing Policy Capacity for Climate Change Adaptation: Governance Arrangements, Resource Deployments, and Analytical Skills in Canadian Infrastructure Policy Making. Issue 1 (9th January 2013) - Craft, Jonathan; Howlett, Michael; Crawford, Mark; McNutt, Kathleen
Abstract This article examines the infrastructure policy sector's capacity to respond to climate change adaptation through an analysis of the Canadian case. It includes a three‐level examination of capacity: at the macro level through a virtual policy network analysis; at the meso level through examination of the lead department's evolving mandate and resources; and at the micro level through analysis of survey data related to departmental workers policy tasks and attitudes. Four hypotheses across these three levels are set out and tested at the national and subnational levels. Together, the findings suggest that the policy capacity in the Canadian infrastructure sector will be unable to meet the demands placed upon the sector to respond to the increasing challenges of climate change adaptation.